EFEKTIVITAS EKSTRAK Padina australis SEBAGAI ANTIBAKTERI Vibrio cholerae DAN Salmonella typhi - Tri Saptari Haryani; - Triastinurmiatiningsih; Weni Ardiani (Ekologia: Jurnal Ilmiah Ilmu Dasar dan Lingkungan Hidup, 2015)
The current utilization of natural materials as a traditional medicine in Indonesia. Aquatic plants has potential as a traditional medicine because it contains active ingredients that are good for health, one of them namely, Padina australis Hauck.The purpose of this study is to establish the most effective concentration of extract of Padina australis as Vibrio cholerae antibacterial and Salmonella typhi. Extract of Padina australis is made by maceration method. Test of the effectivity of extract of Padina australis against Vibrio cholerae and Salmonella typhi. Disc diffusion method Kirby Bauer at the treatment the extract concentration of 50%, 60%, 70%, 80% and control. Results of testing the extract Padina australis against Vibrio cholerae showed a concentration of 80% is the concentration forming the greatest drag areas namely 19.48 mm, while the test results against Salmonella typhi bacteria extract at concentrations of 80% obtained a diameter drag area of 12 mm.Â Key words : antibacterial, Padina australis Hauck, Vibrio cholerae, and Salmonella typhi.